Protons as Second Messenger Regulators of G Protein Signaling - Isom, Daniel G.; Sridharan, Vishwajith; Baker, Rachael; Clement, Sarah T.; Smalley, David M.; Dohlman, Henrik G. (Molecular cell, 2013)
In response to environmental stress, cells often generate pH signals that serve to protect vital cellular components and reprogram gene expression for survival. A major barrier to our understanding of this process has been the identification of signaling proteins that detect changes in intracellular pH. To identify candidate pH sensors, we developed a computer algorithm that searches proteins for networks of proton-binding sidechains. This analysis indicates that Gα subunits, the principal transducers of G protein-coupled receptor (GPCR) signals, are pH sensors. Our structure-based calculations and biophysical investigations reveal that Gα subunits contain networks of pH-sensing sidechains buried between their Ras and helical domains. Further, we show that proton binding induces changes in conformation that promote Gα phosphorylation and suppress receptor-initiated signaling. Together, our computational, biophysical, and cellular analyses reveal an unexpected function for G proteins as mediators of stress-response signaling. •Cellular pH is altered by nutritional and metabolic stress•A structure-based algorithm predicts pH sensing by Gα proteins•Proton binding alters Gα conformation, phosphorylation, and signal transmission•G proteins serve as integrators of receptor- and stress-mediated cell signaling